An RNA element at the 5'-end of the poliovirus genome functions as a general promoter for RNA synthesis. - Dorothee A Vogt; Raul Andino (PLoS Pathogens)
RNA structures present throughout RNA virus genomes serve as scaffolds to organize multiple factors involved in the initiation of RNA synthesis. Several of these RNA elements play multiple roles in the RNA replication pathway. An RNA structure formed around the 5'- end of the poliovirus genomic RNA has been implicated in the initiation of both negative- and positive-strand RNA synthesis. Dissecting the roles of these multifunctional elements is usually hindered by the interdependent nature of the viral replication processes and often pleiotropic effects of mutations. Here, we describe a novel approach to examine RNA elements with multiple roles. Our approach relies on the duplication of the RNA structure so that one copy is dedicated to the initiation of negative-strand RNA synthesis, while the other mediates positive-strand synthesis. This allows us to study the function of the element in promoting positive-strand RNA synthesis, independently of its function in negative-strand initiation. Using this approach, we demonstrate that the entire 5'-end RNA structure that forms on the positive-strand is required for initiation of new positive-strand RNAs. Also required to initiate positive-strand RNA synthesis are the binding sites for the viral polymerase precursor, 3CD, and the host factor, PCBP. Furthermore, we identify specific nucleotide sequences within "stem a" that are essential for the initiation of positive-strand RNA synthesis. These findings provide direct evidence for a trans-initiation model, in which binding of proteins to internal sequences of a pre-existing positive-strand RNA affects the synthesis of subsequent copies of that RNA, most likely by organizing replication factors around the initiation site.